Distance learning with MOODLE system: theoretical and practical aspects (Journal of Information Technologies in Education (ITE), 2007)
The urgency of the issue, considered in the article, is determined by the world process of transition from industrial to information society and by social and economic evolution of Ukraine that demand essential changes in many spheres of the State activity. In order to achieve positive results, particularly in education, it is required to develop system of distance learning at a quick pace. This article considers and analyses distance learning system requirements in conditions of the educational institution and the choice of the most effective distance learning support system is grounded.